2023
DOI: 10.1101/gr.277663.123
|View full text |Cite
|
Sign up to set email alerts
|

Historical RNA expression profiles from the extinct Tasmanian tiger

Abstract: Palaeogenomics continues to yield valuable insights into the evolution, population dynamics, and ecology of our ancestors and other extinct species. However, DNA sequencing cannot reveal tissue-specific gene expression, cellular identity, or gene regulation, only attainable at the transcriptional level. Pioneering studies have shown that useful RNA can be extracted from ancient specimens preserved in permafrost and historical skins from extant canids, but no attempts have been made so far on extinct species. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 109 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…The field of historical RNA is in its infancy. The recent sequencing of the Tasmanian tiger transcriptome has demonstrated that expression profiles can be obtained from museum collections ( Mármol-Sánchez et al , 2023 ). Historical RNA provides a new source of gene expression data, provides new data for microRNA prediction and enables superior genome annotation of rare or extinct species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The field of historical RNA is in its infancy. The recent sequencing of the Tasmanian tiger transcriptome has demonstrated that expression profiles can be obtained from museum collections ( Mármol-Sánchez et al , 2023 ). Historical RNA provides a new source of gene expression data, provides new data for microRNA prediction and enables superior genome annotation of rare or extinct species.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other approaches to analysis of population structure, conStruct incorporates spatial information into the analysis. A complementary approach to analysing and visualizing isolation by distance was conducted using FEEMS, which complements conStruct because it is robust to sparse sampling and functions well under simulated coalescent processes ( Marcus et al , 2021 ). FEEMS determines whether the amount of genetic distance between individuals is what would be expected based on geographical distance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, epigenetic modifications can mediate environmental effects on phenotypes through gene expression and historical epigenomics may therefore allow ancestral patterns of gene expression to be inferred (e.g., Hahn et al., 2023; Rubi et al., 2020). These analyses could be coupled with direct reconstruction of gene expression profiles from natural history specimens (e.g., Marmol‐Sanchez et al., 2023), which is now possible, thanks to the development of protocols for extracting RNA from preserved specimens (e.g., Speer et al., 2022). DNA methylation patterns have already been investigated in ancient and historical specimens (e.g., Gokhman et al., 2014; Gokhman et al., 2016; Hahn et al., 2020; Niiranen et al., 2022; Orlando et al., 2015; Pedersen et al., 2014; Rubi et al., 2020; Smith et al., 2014), indicating that this approach holds promise for unravelling the role of heritable epigenetic modifications in facilitating rapid adaptation to environmental shifts.…”
Section: Applications Of Temporal Data In Invasion Biologymentioning
confidence: 99%